KOMPETENSI KEPRIBADIAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBINA AKHLAK PESERTA DIDIK - Tengku Ari Rafi (UNISAN JURNAL, 2024)
This exploration means to portray the character abilities of Islamic strict schooling educators in creating understudy ethics. This examination utilizes a subjective clear exploration approach in regards to the job of educators in encouraging strict way of behaving by gathering information from essential information sources, specifically educators and understudies, while optional sources incorporate perception, meetings and documentation with information assortment strategies, in particular information decrease and show and check of information in professional schools. . The Koran and Regular Da’wah. The consequences of this examination demonstrate that (1) educators play had an impact in cultivating understudies’ strict way of behaving, as directing educators giving inspiration to understudies to do great strict way of behaving during the educating and educational experience, being well mannered and respectful as would be natural for them. also, deeds. In strict way of behaving, educators go about as counselors and coaches for understudies to do strict way of behaving, including Duha petitions, congregational supplications both at the madrasa and at home, giving aid, giving to retain supplications, fasting, giving charity, and perusing the Koran. what’s more, doing ROHIS exercises at the Sekolah on Friday